2013
DOI: 10.4081/jlimnol.2013.e44
|View full text |Cite
|
Sign up to set email alerts
|

Zooplankton characterisation of Pampean saline shallow lakes, habitat of the Andean flamingoes

Abstract: The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…However, the general tendency was for low-density values of all groups, especially for Rotifers, which were well represented in species but not in abundance. The genera found to be dominant, such as Boeckella, Cephalodella, or Brachionus, have been reported as saline tolerant in previous studies [145,149,150], which is consistent with the information reported here.…”
Section: Biological Communities' Characterizationsupporting
confidence: 92%
“…However, the general tendency was for low-density values of all groups, especially for Rotifers, which were well represented in species but not in abundance. The genera found to be dominant, such as Boeckella, Cephalodella, or Brachionus, have been reported as saline tolerant in previous studies [145,149,150], which is consistent with the information reported here.…”
Section: Biological Communities' Characterizationsupporting
confidence: 92%
“…Most probably, these larvae belong to an undescribed species parasitizing flamingos. Its description requires examination of adult cestodes from their most probable definitive host, Chilean Flamingo Phoenicopterus chilensis Molina, which is abundant in hypersaline shallow lakes from Central Argentina to southern Chilean Patagonia (Battauz et al, 2013; Gibbons, Vilina & Cárcamo, 2007). The remaining two species of flamingos, Andean flamingo Phoenicoparrus andinus and James’ Flamingo Phoenicoparrus jamesi (Sclater), live in the high altitudes of the Andean plateaus of Peru, Chile, Bolivia and Argentina and the probability to be hosts of the species recorded in brine shrimps in Patagonia is low.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the abundance of James's flamingo is higher in alkaline lagoons (Frau et al 2015), shallow and hypersaline lakes, with a higher presence of diatoms and cyanobacteria but scarcity of zooplankton (Caziani and Derlindati 2000). On the other hand, the Chilean flamingo is a selective predator that feeds on larger macrophytes and zooplankton, and is generally found in deep lakes, while the Andean flamingo is non-selective and is found in shallow lakes (Battauz et al 2013;Caziani and Derlindati 2000). Additionally, it has been observed that the abundance of flamingos increases when the water level decreases (Romano et al 2017).…”
Section: Discussionmentioning
confidence: 99%